OPTIMIZATION OF PACKAGING CARTON PRODUCTION AT PT X WITH THE HUNGARIAN METHOD AND MULTI ATTRIBUTE UTILITY THEORY (DINAMIS, 2023)
Household shopping activities in Indonesia have increased by 51% percent since the pandemic period (BPS, 2022). The increase affects household ingredients in packaging.  PT X produces various types of packaging for household needs with various size specifications through the make to order system has experienced an overload of production quantity resulting in a delay of 36.19%.  PT X needs to conduct problem analysis and production planning to improve ontime delivery. Problem analysis is carried out by direct observation methods and management interviews. Production planning is carried out by dividing and prioritizing tasks using the Hungarian optimization method and Multi Attribute Utility Theory